2021
DOI: 10.1007/s11071-021-06777-6
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the impact of environmental stresses on the frequent waves of COVID19

Abstract: A novel approach to link the environmental stresses with the COVID-19 cases is adopted during this research. The time-dependent data are extracted from the online repositories that are freely available for knowledge and research. Since the time series data analysis is desired for the COVID-19 time-dependent frequent waves, here in this manuscript, we have developed a time series model with the aid of "nonlinear autoregressive network with exogenous inputs (NARX)" approach. The distribution of infectious agent-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The researchers [ 14 , 18 ] assessed the impact of the environmental stressors such as the impact of ozone, impact of nitrogen present in the environment, and other factors, on the spread of this enveloped virus. Another group of researchers [ 5 ] discussed the impact of pollution as well as the temperature, on the spread of this virus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers [ 14 , 18 ] assessed the impact of the environmental stressors such as the impact of ozone, impact of nitrogen present in the environment, and other factors, on the spread of this enveloped virus. Another group of researchers [ 5 ] discussed the impact of pollution as well as the temperature, on the spread of this virus.…”
Section: Resultsmentioning
confidence: 99%
“…To be more explicit, different variants of coronavirus exist in the world with different properties and characteristics since 1962 [ 1 , 6 , 14 , 16 , 17 , 19 – 23 ]. According to the recent studies, the major variants that are extensively reported are: the Alpha Variant (formerly called the UK Variant and officially known as B.1.1.7) , Variant (South Africa Variant/ B.1.351), Variant (Brazil Variant, officially known as P.1), and the Variant (India Variant and officially known as B.1.617.2).…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the training of neural networks will be easier when the capability of computation is improved. The proposed method can be employed to study big data access control in social networks (Yu et al 2021a ; Yang et al 2020 ) and CoVID-19 (Yu et al 2021b , c , d ).…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical models are important tools for predicting and simulating the spread of epidemics, and can provide a theoretical basis for decision-makers to formulate various epidemic prevention measures. There are many mathematical models related to the spread of COVID-19, such as those in [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . There are also some studies on the impact of vaccination on the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%